Green Photonics and Electronics - Eisenstein, Gadi.; Bimberg, Dieter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This books focuses on recent break-throughs in the development of a variety of photonic devices, serving distances ranging from mm to many km, together with their electronic counter-parts, e.g. the drivers for lasers, the amplifiers following the detectors and most important, the relevant advanced VLSI circuits. It explains that as a consequence of the increasing dominance of optical interconnects for high performance workstation clusters and supercomputers their complete design has to be revised. This book thus covers for the first time the whole variety of interdependent subjects contributing to green photonics and electronics, serving communication and energy harvesting. Alternative approaches to generate electric power using organic photovoltaic solar cells, inexpensive and again energy efficient in production are summarized. In 2015, the use of the internet consumed 5-6% of the raw electricity production in developed countries. Power consumption increases rapidlyand without some transformational change will use, by the middle of the next decade at the latest, the entire electricity production. This apocalyptic outlook led to a redirection of the focus of data center and HPC developers from just increasing bit rates and capacities to energy efficiency. The high speed interconnects are all based on photonic devices. These must and can be energy efficient but they operate in an electronic environment and therefore have to be considered in a wide scope that also requires low energy electronic devices, sophisticated circuit designs and clever architectures. The development of the next generation of high performance exaFLOP computers suffers from the same problem: Their energy consumption based on present device generations is essentially prohibitive.
Energy-efficient Vertical-cavity Surface-emitting Lasers for Optical Interconnects -- High-speed InP-based Long-wavelength VCSELs -- Quantum-Dot Semiconductor Optical Amplifiers for Energy-Efficient Optical Communication -- Quantum‐Dot Mode‐Locked Lasers: Sources for Tunable Optical and Electrical Pulse Combs -- Nanophotonic Approach to Energy-Efﬁcient Ultra-Fast All-Optical Gates.
Keywords: Renewable energy sources; Lasers; Electric power production; Microprocessors; Computer architecture; Renewable Energy; Laser; Electrical Power Engineering; Processor Architectures; Mechanical Power Engineering